Moderating Effect of Perceived Remaining Time in the Relationship between Job Demands and Job Stress - Luthfia Putri Rizki; Debora Eflina Purba (Asian Academy of Management Journal, 2022)
This study aims to investigate the moderating effect of perceived remaining time on the relationship between job demands and job stress. Using the Conservation of Resources (COR) theory to explain the moderation effect, we argue that the relationship between job demands and job stress is weakened by perceived remaining time. Data were collected using online survey on public sector employees from 32 government institutions in Indonesia (N = 220). Data were analysed using Hayes’ PROCESS macro on SPSS software. Results showed that perceived remaining time moderated the relationship between job demands and job stress, such that the relationship was positive and higher when perceived remaining time was low than when perceived remaining time was high. Theoretical and practical implications are further discussed.